2021
DOI: 10.3389/fphar.2021.676239
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase Inhibitors: A Review of Their Anti-Inflammatory Therapeutic Potential and Mechanisms of Action

Abstract: Chronic inflammatory diseases are debilitating, affect patients’ quality of life, and are a significant financial burden on health care. Inflammation is regulated by pro-inflammatory cytokines and chemokines that are expressed by immune and non-immune cells, and their expression is highly controlled, both spatially and temporally. Their dysregulation is a hallmark of chronic inflammatory and autoimmune diseases. Significant evidence supports that monoamine oxidase (MAO) inhibitor drugs have anti-inflammatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 177 publications
0
45
0
Order By: Relevance
“…Induction of P/DAMP signaling drives epithelial cells to express pro-inflammatory cytokines and chemokines such as interleukin-1 β (IL-1β), tumor necrosis factor- α (TNF-α), interleukin-6 (IL-6) and interleukin-8 (IL-8) ( Borish and Steinke, 2003 ; Kugelberg, 2014 ; Groeger and Meyle, 2019 ; Plemmenos et al, 2021 ). Significant evidence supports that reduction of monoamine oxidase enzyme function by MAO inhibitors decreases innate immune-based cytokine signaling and positively improves disease progression ( Ostadkarampour and Putnins, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of P/DAMP signaling drives epithelial cells to express pro-inflammatory cytokines and chemokines such as interleukin-1 β (IL-1β), tumor necrosis factor- α (TNF-α), interleukin-6 (IL-6) and interleukin-8 (IL-8) ( Borish and Steinke, 2003 ; Kugelberg, 2014 ; Groeger and Meyle, 2019 ; Plemmenos et al, 2021 ). Significant evidence supports that reduction of monoamine oxidase enzyme function by MAO inhibitors decreases innate immune-based cytokine signaling and positively improves disease progression ( Ostadkarampour and Putnins, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have also demonstrated that MAO inhibitors decrease gene and protein expression of a number of pro-inflammatory cytokines and chemokines. This reduction in drivers of inflammation may have therapeutic potential ( Ostadkarampour and Putnins, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…MAO inhibitors also increase biogenic amines such as dopamine and this increase can modify immune responses (Ostadkarampour and Putnins, 2021). Dopamine signaling can act in a receptor-dependent and also receptorindependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of P/DAMP signaling drives epithelial cells to express pro-inflammatory cytokines and chemokines such as interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-8 (IL-8) (Borish and Steinke, 2003;Kugelberg, 2014;Groeger and Meyle, 2019;Plemmenos et al, 2021). Significant evidence supports that reduction of monoamine oxidase enzyme function by MAO inhibitors decreases innate immune-based cytokine signaling and positively improves disease progression (Ostadkarampour and Putnins, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation